High Throughput Technology: Exemplary Highlights of Advanced Technical Tools. Issue 7 (11th June 2014) - Titlbach, Sven; Futter, Cornelia; Lejkowski, Michael; Lange de Oliveira, Armin; Schunk, Stephan Andreas; Nilles, Michael; Wozny, Günter
Abstract High throughput experimentation in catalysis and materials science has evolved into a mature technology platform. This article provides a technology‐focused mini‐review of three specific exemplary highlights, such as the purification of heavy feedstocks via hydroprocessing, the debottlenecking of workflows by smart use of alternative technologies, and the development of new mass screening devices. The approaches presented here clearly demonstrate their specific potential for accelerating research and show what level of sophistication has been reached since the early beginnings.